The Effect of Shuttle Run and Zig Zag Run Exercises and Confidence on Passing Productivity on Tanjungbalai FC Pumata Futsal Players - Muhammad Amin Syahputra; Sanusi Hasibuan; Novita Novita (Universitas Negeri Medan, 2021)
The focus of this study aims to determine the effect of shuttle run, and zig-zag run training and self-confidence on passing productivity in Futsal players Pumata FC Tanjungbalai trying to improve athlete achievement among teenagers. This study uses an experimental research method by level 2 x 2, so the hypothesis submission is carried out using a two-way analysis of variance (ANAVA). After that, hypothesis testing was carried out using a two-way analysis of variance (ANAVA). This research was carried out at the PUMATA FC Team's training ground which was located at the Tanjungbalai city futsal field. The implementation time is about four weeks, with meetings three times a week. The sample of this research is all Pumata FC players consisting of 20 people who are given shuttle run training and zig-zag run training. Based on the analysis results above, it shows that there are differences in mean in the four groups by giving shuttle run and zig-zag run exercises. The highest mean value was obtained in the high self-confidence group trained with the zig-zag run, which was 8.60 (if rounded up to 9 successful passes). Meanwhile, the lowest mean value was obtained in the low self-confidence group trained with the shuttle run, which was 6.20 (if rounded up to 6 successful passes).